A prospective randomized open‐label trial on the comparative effects of 6% hydroxyethyl starch 130/0.4 versus polyionic isotonic crystalloids on coagulation parameters in dogs with spontaneous hemoperitoneum. Issue 1 (27th October 2020) - Iannucci, Claudia; Dirkmann, Daniel; Howard, Judith; Adamik, Katja N.
Abstract: Objective: To evaluate the effects of 6% hydroxyethyl starch 130/0.4 (HES) and a polyionic isotonic crystalloid (CRYS) on standard coagulation tests and rotational thromboelastometry (ROTEM) in dogs with spontaneous hemoperitoneum (SHP). Design: Prospective randomized open‐label clinical study. Setting: University teaching hospital. Animals: Forty‐two client‐owned dogs presented with SHP. Interventions: Dogs diagnosed with SHP and hypovolemic shock were randomly allocated to receive HES (10 mL/kg, n = 22) or CRYS (30 mL/kg, n = 20) intravenously over 20 minutes for hemodynamic stabilization. Measurements and main results: Parameters measured before (T0 ) and after (T1 ) treatment were HCT, platelet counts, prothrombin time, activated partial thromboplastin time, fibrinogen concentrations, and extrinsic activated (EXTEM), intrinsic activated (INTEM), and extrinsic activated with platelet inhibition ROTEM assays. Data were analyzed as absolute values and as the percentage change from T0 to T1 . No significant differences between groups were detected in any variable at T0, and for HCT, platelet counts, prothrombin time, activated thromboplastin time, and fibrinogen concentrations at T1 . Clot formation time in EXTEM was significantly prolonged ( P  = 0.037), and maximum clot firmness was significantly decreased ( P  = 0.038) in the HES group compared to the CRYS group at T1 . The percentage change in EXTEM clotting time ( P  = 0.012) and INTEM clot formation time ( P  = 0.031) was greater after HES than CRYS. Lysis indices remained at 100% for all ROTEM assays in both groups. Conclusion: Compared to a 3‐fold volume of CRYS, administration of HES was associated with impairment in ROTEM parameters in dogs with SHP, but no evidence of hyperfibrinolysis was detected.